THE DEVELOPING MATH ELECTRONIC MODULE WITH SCIENTIFIC APPROACH USING KVISOFT FLIPBOOK MAKER PRO FOR XI GRADE OF SENIOR HIGH SCHOOL STUDENTS - Aulia Fonda; Sumargiyani Sumargiyani (IKIP Siliwangi and I-MES, 2018)
This study aims to determine the feasibility of learning media electronic module (e-module) based on Kvisoft Flipbook Maker Pro on derivative material with Scientific approach using Research and Development research methodology. The study was conducted in two schools by taking 4 students as a student response in small classes and 20 students in a large class. The research instrument used in the form of evaluation formative form of teaching materials for material experts, media experts, and student responses. From the result of the assessment of expert material instrument obtained an average score of 101.25 with very good criteria, the assessment of expert media instruments obtained an average score of 116 with good criteria as well as on student response instruments obtained 86.44 with very good criteria. These results indicate that the e-module of mathematics with the scientific approach of the derived material for the XI class of the even semester high school is worthy of use in the process of learning in the classroom.